IJCM_37A: Perception and knowledge regarding poly-cystic ovarian syndrome among health science students in Mangalore - Rathee Dipanshu; Priya Aditi; Gupta Aviral; Rajeev Akshara; Grover Shuchi; Motappa Rohith; Rekha T; Unnikrishnan Bhaskaran; Mithra Prasanna; Kumar Nithin; Holla Ramesh; Rao Mithun (Wolters Kluwer Medknow Publications, 2024)
Background: The incidence of PCOS among females is increasing. Awareness among women about PCOS can help in early diagnosis and prevention by making lifestyle modifications. Lifestyle modifications not only help in prevention of disease but also in managing the symptoms and complications. Objectives: 1. To find out the perception regarding PCOS among students of different courses. 2. To assess the knowledge about PCOS among students Methodology: A cross-sectional study on Undergraduate medical, dental and allied health sciences students enrolled in KMC, Mangalore and MCODS, Mangalore Results: 12.6% of the students had a family history of PCOS. 85% of the students have heard about PCOS. Out of the people who have heard about PCOS 20% have been diagnosed with it. Out of the people who have heard about PCOS, most of the students knew that PCOS is associated with irregular periods, infertility, mood swings and hormonal disturbances. Conclusion: Awareness about PCOS is maximum among MBBS students followed by AHS and then BDS students.